(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
The study revealed that the highest average yield, 36.6 q/ha, was obtained in the variant where the Fitovak 20% immunostimulant was applied at the rate of 0.6+0.7+0.8 L/ha. This yield was higher than those recorded in the variants treated with the Biodux and MERS biostimulants. In the variants where the MERS biostimulant was applied at three different rates, the yield was 0.5, 0.8 and 1.0 q/ha lower than in the variants treated with the Fitovak 20% immunostimulant at three different rates. However, compared with the variants treated with the Biodux biostimulant at three different rates, the MERS biostimulant provided an additional yield increase of 3.7, 4.4 and 4.1 q/ha.